KEBIJAKAN HUKUM PIDANA TERHADAP TINDAK PIDANA PENCEMARAN NAMA BAIK DALAM UNDANG-UNDANG NO. 40 TAHUN 1999 TENTANG PERS DIKAITKAN DENGAN ASAS KEPASTIAN HUKUM - Wiby Fitria Alda; Davit Rahmadan; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Criminal law policy in the press is still a problem for the press and society. The absence of regulations governing clear criminal sanctions against criminal acts of defamation committed by the press in Law No. 40 of 1999 concerning the current press. Currently, they still use regulations from other laws such as the Criminal Code, the Information and Electronic Transactions Law of 2016. The sanctions for criminal defamation vary in each regulation. So that there is no legal certainty for the press and the public. So that there will be no more debates between the press and the public if problems occur between them, it can be resolved according to the law per situ itself and provide legal certainty for Law No. 40 of 1999 About the Press. So that the creation of justice in society. This research uses the typology of normative legal research or also called doctrinal legal research, which more specifically discusses legal principles. In this study the author uses the nature of descriptive research, because the author describes the Criminal Law Policy Against the Crime of Defamation in Law. No. 40 of 1999 About the Press Related to the Principle of Legal Certainty. The results of the research conducted by the author, Law No. 40 of 1999 concerning the Press which should be supplemented with regulations in it such as regulations governing criminal defamation carried out by the press and what are the sanctions so that it can be said to be a lex specialist and give effect. deterring press people who are not professional in carrying out their duties. The criminal law policy given to the people of the press aims to maintain order in society and improve the personality of the perpetrator. The government should make the formulation of criminal sanctions in the current press law that can be applied. and Judges are judges in sanctions against press offenses to put more emphasis on the press law.Keywords: Criminal Law Policy - Press - Crime – Defamati